MASTERING VERBS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE TO NATIVE SPEAKERS OF THE UZBEK LANGUAGE FUTURE TRANSLATION SPECIALISTS IN UZBEK/ENGLISH/RUSSIAN (Web of Teachers: Inderscience Research, 2025)
For the Russian verbs to be studied by the future translators whose mother-tongue is Uzbek, we grouped these verbs by the analogies of conjugation forms and trained them in studying and communicative situations to make the students interiorize the algorithm. A next mechanism helping memorize the lexemes of the language of another family was using etymologically relative words in Russian and in English as an intermediary language, in some cases also Turkic and Persian words known by the students due to their presence in Uzbek. The methodology showed creating a good command of Russian verbal forms.